THE DIFFERENCE IN AGE GROUPS DURING LEARNING A LANGUAGE AS A SECOND LANGUAGE - Turgunov, Shukhratjon (INTERNATIONAL CONFERENCES, 2023)
In this article describes that two different age groups in a learning zone and discusses benefits and difficulties while learning language. In addition, solution is given by author.